Incidence of new osteoporotic adjacent vertebral body fractures. A comparison between conservative treatment and vertebral body augmentation (vertebroplasty, kyphoplasty): a systematic review and meta-analysis - Korovessis, Panagiotis; Syrimpeis, Vasileios; Korovesis, Alkis; Dimakopoulos, Georgios (Frontiers in Surgery, 2025)
Study designA Systematic Review and Meta-AnalysisPurposeTo compare the incidence of New Adjacent Vertebral Fractures (ANVFs) in elderly patients with Osteoporotic Vertebral Compression Fractures (OVCFs) undergoing either percutaneous vertebral augmentation—via Vertebroplasty (PVP) or Kyphoplasty (PKP)—or Conservative Treatment (CT). Additionally, this study aims to identify potential risk factors associated with ANVFs.HypothesisThe incidence of ANVFs does not significantly differ between patients managed with CT and those treated with PVP or PKP.BackgroundWhile the optimal treatment for OVCFs remains debated, PVP and PKP offer immediate stabilization, pain relief, and may help correct vertebral body wedging with minimal complications. However, a review of the literature reveals a limited number of meta-analyses comparing CT with PVP/PKP regarding the incidence of ANVFs.Materials and methodsFollowing PRISMA guidelines, a systematic search was conducted across PubMed, Cochrane, Web of Science, Scopus and Science Direct to identify studies published between 2005 and 2024 comparing surgical treatment with CT for ANVFs incidence. Nine studies (five RCTs and four retrospective comparative case-control studies) involving 1,930 patients were included in the analysis.ResultsIn RCTs, the analysis indicated a significant difference (P < 0.05) in ANVFs incidence favoring the surgical group, with a Relative Risk (RR) of 0.66 (95% CI: 0.44–0.99; P = 0.05); in retrospective studies, no statistically significant difference was found between the surgical and CT groups (OR = 0.87, 95% CI: 0.58–1.31; P = 0.51). Differences in study parameters such as age, total number of participants, surgical approach (unilateral vs. bilateral), etc. were observed but they could not be accurately tested due to the limited number of studies.ConclusionThis meta-analysis, for the selected RCTs, shows that vertebral augmentation is associated with a lower incidence of ANVFs compared to CT. On the other hand, in the retrospective studies group there was no significant difference in the incidence of ANVFs between the two treatment groups (CT vs. PKP/PVP). Variations in study parameters, such as patient demographics and surgical techniques, may have affected these results. Further high-quality studies are needed to better understand the long-term effects of different treatment strategies on the incidence of ANVFs.Systematic Review RegistrationPROSPERO (CRD420250509815).